Clinical behavior of recurrent hormone receptor–positive breast cancer by adjuvant endocrine therapy within the Breast International Group 1‐98 clinical trial. Issue 5 (8th December 2020) - Leone, Jose P.; Cole, Bernard F.; Regan, Meredith M.; Thürlimann, Beat; Coates, Alan S.; Rabaglio, Manuela; Giobbie‐Hurder, Anita; Gelber, Richard D.; Ejlertsen, Bent; Harvey, Vernon J.; Neven, Patrick; Láng, Istvan; et al.
Abstract : Background: Endocrine therapy resistance is a major cause of distant recurrence (DR) in hormone receptor–positive breast cancer. This study evaluated differences in survival after DR in patients treated with different adjuvant endocrine therapy regimens in the Breast International Group (BIG) 1‐98 trial. Methods: BIG 1‐98 compared 5 years of adjuvant treatment among 4 arms: tamoxifen (T), letrozole (L), tamoxifen followed by letrozole (TL), and letrozole followed by tamoxifen (LT). After a median follow‐up of 8.1 years, 911 of 8010 patients (T, 302; L, 285; TL, 170; and LT, 154) had DR as the site of first recurrence. Univariate and multivariate Cox analyses were performed to determine features associated with post‐DR survival. Results: The median follow‐up time after DR was 59 months (interquartile range, 29‐88 months). Among all patients with DR, 38.1% were 65 years old or older at enrollment, 61.9% had tumors larger than 2 cm, and 69.7% were node positive. Neoadjuvant or adjuvant chemotherapy was administered to 35.6% of the patients. There was no difference in post‐DR survival by treatment arm (median survival, 20.8 months for T, 17.9 months for L, 17.3 months for TL, and 20.8 months for LT; P = .21). In multivariate analysis, older patients (hazard ratio [HR], 1.35; 95% confidence interval [CI], 1.15‐1.59) and patients with tumors larger than 2 cm (HR, 1.19; 95% CI, 1.00‐1.41), 4 or more positive nodes (HR, 1.31; 95% CI, 1.05‐1.64), progesterone receptor (PR)–negative tumors (HR, 1.25; 95% CI, 1.02‐1.52), or shorter disease‐free survival (DFS) had significantly worse post‐DR survival. Conclusions: Treatment with adjuvant T, L, or their sequences was not associated with differences in survival after DR. Significant differences in survival were observed by age, primary tumor size, nodal and PR status, and DFS, and this suggests that traditional baseline high‐risk features remain prognostic in the metastatic setting. Abstract : In the Breast International Group 1‐98 study, no difference was observed in post–distant recurrence survival by adjuvant endocrine treatment arm. Older patients and patients with tumors larger than 2 cm, 4 or more positive nodes, progesterone receptor–negative tumors, or shorter disease‐free survival had significantly worse post–distant recurrence survival.